High prevalence of non-alcoholic fatty liver disease (NAFLD) among Gujarati Indians in North London: a population-based study. (1st January 2017) - Neukam, Karin; Bhagani, Sanjay; Rodger, Alison; Oben, Jude; Nirmal, Divyabala; Jain, Anjly; Nair, Devaki R.
ABSTRACT: Background: The prevalence of non-alcoholic fatty liver disease (NAFLD) among Indian Asians in high-income countries is not well studied, but appears to be different from that for Western populations.Design: Cross-sectional study of subjects recruited through a community cardiovascular (CV) screening programme at two London Hindu temples from 2010–2012. NAFLD was diagnosed using the fatty liver index (FLI) and fibrosis stage through the BARD (Body Mass Index (BMI), Aspartate aminotransferase to Alanine aminotransferase ratio and Diabetes Mellitus) score.Results: 597 subjects were assessed; 306 (51%) female. Median (interquartile range) age and BMI were 49 (40.6–55.0) years and 26.4 (23.5–29.2) kg/m 2, respectively. NAFLD was diagnosed in 184 (30.8%) cases, but 175 (29.3%) subjects could not be categorised. Overall, 117 (40.2%) men and 67 (21.9%) women had evidence of NAFLD ( p  < 0.001). In those with evidence of NAFLD, 142 (78.5%) had a BARD score suggestive of advanced fibrosis. Advanced fibrosis could be excluded in 5 (7.6%) women and 34 (29.6%) men ( p  < 0.001). Total cholesterol (TC), triglycerides (TG) and non-HDL (high-density lipoprotein cholesterol) were higher in the NAFLD group ( p  < 0.001), whereas HDL-C was lower ( p  < 0.001).Conclusion: There is evidence of a high prevalence of asymptomatic NAFLD, possibly in combination with advanced liver damage, among UK-based Gujarati Indians living in London. NAFLD is emerging as an independent risk factor for CV disease. Screening programmes should be developed in order to decrease liver and CV mortality and morbidity in these high-risk patients.